RISK FACTORS FOR DEVELOPMENT OF RETINOPATHY OF PREMATURITY IN TWINS ATTENDING A TERTIARY CARE CENTRE IN KASHMIR (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Retinopathy of Prematurity (ROP) is a leading cause of preventable childhood blindness, primarily affecting preterm and low birth weight infants. The disorder results from abnormal retinal vascular development, triggered by premature birth and postnatal oxygen exposure, which disrupts the normal angiogenic process of the retina. Aim: To study the risk factors associated with the development of retinopathy of prematurity in twin babies. Methods: This retrospective observational study included preterm twin neonates who fulfilled the Rashtriya Bal Swasthya Karyakram (RBSK) screening criteria for Retinopathy of Prematurity (ROP). Results: The study analyzed50 twin pairs (100 infants) with gestational age34 weeks who fulfilled the inclusion criteria. It was observed that besides known risk factors like lower gestational age, low birth weight, prolonged mechanical ventilation, sepsis, transfusions and oxygen supplementation,twin-twin transfusion syndrome as well as birth weight discordance (20%), a key finding in our study, was significantly associated with the development of ROP (p=0.03). Conclusion: This hospital-based study highlights the high-risk factors and complexity of Retinopathy of Prematurity (ROP) in twin pregnancies, particularly among monochorionic (MC) twins and those complicated by twin-to-twin transfusion syndrome (TTTS) and birth weight discordance. Key risk factors—lower gestational age, birth weight